The New French Law of Contract - Rowan, S (Oxford University Press, 2022)
After being almost untouched for over 200 years, the contract law section of the French Civil Code was overhauled in 2016 and 2018. The New French Law of Contract describes, explains, and analyses the new general principles of contract law in the reformed Code in a concise and stimulating way. The areas covered include contract formation, validity, the interpretation and supplementation of terms, the regulation of unfair terms, privity of contract, change of circumstances, breach of contract, and remedies. The book examines the ways in which the new articles affirm or depart from the provisions of the 1804 Code and pre-reform case law, giving special attention to changes that have proved to be controversial and the debates that surround them. It also considers the various influences that have shaped the reforms, in particular those from international contract law instruments such as the Principle of European Contract Law and the UNIDROIT Principles. Written from the standpoint of a common lawyer, the book is designed to help readers from a common law background to navigate the innovations in the reforms and the new French law of contract that emerges. It is essential reading for students, researchers, practitioners, law-makers, and judges with an interest in comparative law.